The Triumph of Music, and Other Lyrics - Cawein, Madison Julius, 1865-1914 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Triumph of Music and Other Lyrics" by Madison Julius Cawein is a collection of lyrical poetry written in the late 19th century. The book encompasses a variety of themes including love, nature, longing, and the transcendental power of music. Through his verses, Cawein explores emotional landscapes that resonate with both the beauty and melancholy of existence, inviting readers into a world of lyrical enchantment. The opening portion of the collection sets a rich, atmospheric tone that intertwines nature and music with deep emotional resonance. It begins in a picturesque valley where the poet observes a garden filled with vibrant flowers and echoing fountains, capturing the serene beauty of the natural world. As the poet wanders at night, enchanted by the fragrance of blossoms, he encounters a mysterious youth who expresses a profound yearning for music that speaks to the depths of his soul. This poignant encounter introduces themes of love, loss, and the captivating power of art, establishing the collection as a lyrical exploration of both inner and outer landscapes. (This is an automatically generated summary.)
Release date is 2011-09-10
E-text prepared by David Garcia, Josephine Paolucci, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Kentuckiana Digital Library (http://kdl.kyvl.org)
Keywords: American poetry